Relevansi Pendidikan Akhlak Terhadap Pengintegrasian Nilai Moral Pada Pendidikan Non Formal - Dede Apriyansyah; Erik Novianto; Rahmat Hidayat (IAIN Batusangkar, 2022)
Morals as a mirror for a person, a person's personality is perfect with perfect morals. Moral decline in the social realm of society is beginning to decline not only in individual morality, but also in respect for parents, kindness, and loss of interest in the social environment in which they live. This phenomenon is a type of obstacle that should not be tolerated. This study is a qualitative study, a library study whose main subject is books and other literature. The results showed that moral education is the most important thing to the integration of moral values. The link between moral education and morality is very closely linked. In other words, there is content that is complementary and mutually supportive. Both share basic similarities. That is, both the study and determination of the magnitude of good and evil by considering human behavior that arises not only from formal education but also from informal education.